The post-tourist or tourist of the post-globalization and the trip focus on religious heritage (Journal of the Sociology and Theory of Religion, 2018)
This study pays attention to the phenomenon of the non-crowded tourist who seeks to know the religious heritage (as an anthropological experience), while performing another type of tourism: rural, social (youth or elderly), sports, adventure, genealogical and roots, gastronomic, etc. Thus, the adoption of new cultural patterns in the practice of tourism experiences, increasingly present in the population, is reflected, reflecting the new height of the times and changes in tourism practices.
Keywords: Tourism, Post-globalization, Religious Heritage, Trip.